PENDIDIKAN KARAKTER: KEPEDULIAN TERHADAP LINGKUNGAN - Masduki, Yusron (Conciencia, 2019)
a Karno as the first President of the Republic of Indonesia as the founding father of this nation stressed that: This nation must be built by prioritizing character building, because this character will make Indonesia a great, advanced and dignified nation. If character development is not carried out, then the Indonesian people will become coolies. Character can be interpreted as a basic value that builds a person's personal, formed because of the influence of heredity and environmental influences, which distinguishes it from others, and is manifested in attitudes and behaviors in everyday life.